PLMD: An updated data resource of protein lysine modifications. (20th May 2017) - Xu, Haodong; Zhou, Jiaqi; Lin, Shaofeng; Deng, Wankun; Zhang, Ying; Xue, Yu
Abstract: Post-translational modifications (PTMs) occurring at protein lysine residues, or protein lysine modifications (PLMs), play critical roles in regulating biological processes. Due to the explosive expansion of the amount of PLM substrates and the discovery of novel PLM types, here we greatly updated our previous studies, and presented a much more integrative resource of protein lysine modification database (PLMD). In PLMD, we totally collected and integrated 284, 780 modification events in 53, 501 proteins across 176 eukaryotes and prokaryotes for up to 20 types of PLMs, including ubiquitination, acetylation, sumoylation, methylation, succinylation, malonylation, glutarylation, glycation, formylation, hydroxylation, butyrylation, propionylation, crotonylation, pupylation, neddylation, 2-hydroxyisobutyrylation, phosphoglycerylation, carboxylation, lipoylation and biotinylation. Using the data set, a motif-based analysis was performed for each PLM type, and the results demonstrated that different PLM types preferentially recognize distinct sequence motifs for the modifications. Moreover, various PLMs synergistically orchestrate specific cellular biological processes by mutual crosstalks with each other, and we totally found 65, 297 PLM events involved in 90 types of PLM co-occurrences on the same lysine residues. Finally, various options were provided for accessing the data, while original references and other annotations were also present for each PLM substrate. Taken together, we anticipated the PLMD database can serve as a useful resource for further researches of PLMs. PLMD 3.0 was implemented in PHP + MySQL and freely available athttp://plmd.biocuckoo.org .